(untitled) (CIPEEX, 2022)
ACCORDING TO THE 5TH EDITION OF THE "PORTRAITS OF READING" SURVEY IN BRAZIL, IT SUSTAINED ASIGNIFICANT DROP OF APPROXIMATELY 4.6 MILLION READERS IN BRAZIL BETWEEN 2015 AND 2019.WITH THE RECENT DECLINE IN THE NUMBER OF ACTIVE READERS IN BRAZILIAN TERRITORY, DUE TO LACKOF TIME, OR INTEREST, THERE IS A COMMON PROBLEM. OFTEN THE INDIVIDUAL INTENDS TO READ BUTGIVES UP ON THE WAY BECAUSE HE DOES NOT FIND VIABLE SOURCES OR SPENDS A LOT OF TIME ORMONEY WHENEVER HE WANTS TO FIND AND PURCHASE A BOOK, WHETHER PHYSICAL OR VIRTUAL.GIVEN THIS PREROGATIVE, THE MUNINN INITIATIVE HAS AS ITS MAIN OBJECTIVE TO FACILITATE ANDMAKE READING CONVENIENT WITH THE APPLICATION OF EFFICIENT RESEARCH METHODS, SO THAT THEUSER RESERVES HIS TIME TO READ AND DOES NOT HAVE TO SHARE IT WITH THE SEARCH FOR ITSCONTENT. IN ADDITION TO READING BOOKS, IT ALSO SPENDS ITS TIME IN ITS REVIEWS WITH OTHERUSERS, BEING ABLE TO STORE THE ONES THAT THE USER ALREADY HAS OUTSIDE THE PLATFORM, TOCONCENTRATE ALL THE CONTENT IN ONE PLACE. IN THE DEVELOPMENT OF THE SOFTWARE, THESCRUM METHOD WILL BE USED, WITH A FOCUS ON THE MVP OF THE PRODUCT, CREATED THROUGHUSER STORIES AND TEAM GOALS. FOR THE CHOICE OF THE FUNCTIONALITY TO BE DEVELOPED IN THEWEEK SPRINT, THE ORDER OF PRIORITY AND THE LEVEL OF DIFFICULTY, DEFINED THROUGH PLANNINGPOKER, WILL BE TAKEN INTO ACCOUNT. MUNINN’S VISUAL IDENTITY WAS DESIGNED TO APPEAL TOTHE USER’S COGNITION AND BE INTUITIVE IN ITS FEATURES, AND ITS DEFINITION WAS MADE THROUGHTHE ANALYSIS OF PERSONAS. THE COLORS HAVE LOW SATURATION AND WARM TONES, SO THE EYESFEEL MORE RESTED, FOLLOWING THE PRINCIPLES OF COLOR PSYCHOLOGY. THE BLOCK STRUCTURE OF THE PAGE MAKES IT EASIER FOR THE BRAIN TO UNDERSTAND THE SHAPES, BEING ABLE TOUNDERSTAND THE INTERFACE WITHOUT MUCH EFFORT, FOLLOWING THE GESTALT LAW. SOMEELEMENTS, SUCH AS BOOK COVERS OR DETAILED DESCRIPTIONS, MAY APPEAR PARTIALLY COVEREDIN THE INTERFACE, INDICATING THE IDEA OF CONTINUATION, THUS APPLYING THE UX RULE. THEDIGITAL READER SCREEN HAS ELEMENTS THAT CAN BE HIDDEN FROM THE INTERFACE, FOR FULL FOCUSWHEN READING. THE RESULTS ACHIEVED WERE THE FIRST SCREENS OF THE SITE: THE PROFILE,HOME, AND DIGITAL READER PAGES WERE PROTOTYPED USING THE FIGMA PLATFORM,DEMONSTRATING THE ARRANGEMENT OF ELEMENTS, HOW THE RULES WILL BE APPLIED, AND THEINITIAL LOOK OF THE PLATFORM.